The Entry Blocker Peptide Produced in Chlamydomonas reinhardtii Inhibits Influenza Viral Replication in vitro - Reyes-Barrera, Karen Lizbeth; Soria-Guerra, Ruth Elena; López-Martínez, Rogelio; Huerta, Leonor; Salinas-Jazmín, Nohemí; Cabello-Gutiérrez, Carlos; Alpuche-Solís, Ángel Gabriel (Frontiers in Plant Science, 2021)
This year, a respiratory virus caused an emergency pandemic alert in health services around the world, showing the need for biotechnological approaches to fight these diseases. The influenza virus is one of the main viral agents that generate pandemic outbreaks. Currently, the majority of co-circulating influenza A virus (IAV) strains are adamantine‐ and oseltamivir-resistant strains, and the challenge is to find new antivirals for more efficient treatments. The antiviral entry blocker (EB) peptide is a promising candidate for blocking the virus entry into cells. The aim of this research was to express the EB peptide in the microalgae Chlamydomonas reinhardtii and test its antiviral activity against IAV in vitro. The EB peptide nucleotide sequence was introduced into the nuclear genome of microalgae using Agrobacterium tumefaciens transformation. The EB peptide amount produced in transformed microalgae was 4.99 ± 0.067% of the total soluble protein. In hemagglutination inhibition assays using influenza A/H1N1 pdm and influenza A H1N1/Virginia/ATCC/2009 strains, we reported that the EB peptide extract from the microalgae showed 100-fold higher efficiency than the EB synthetic peptide. In addition, both the EB peptide extract and synthetic peptide inhibited viral replication in MDCK cells (IC50 = 20.7 nM and IC50 = 754.4 nM, respectively); however, the EB peptide extract showed a 32-fold higher antiviral effectiveness than the synthetic peptide against influenza A/H1N1 pdm. Extracts from untransformed and transformed microalgae and synthetic peptide did not show cytotoxic effect on MDCK cell monolayers. Thus, C. reinhardtii may be a fast, safe, and effective expression platform for production of peptides with significant antiviral activity and can be used as a prophylactic treatment to reduce viral propagation.